2019
DOI: 10.1371/journal.pone.0218739
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for repeated hyperkalemia and potassium trajectories in high-risk patients — A population-based cohort study

Abstract: Understanding predictors and trajectories of increased potassium may inform testing and treatment of hyperkalemia. We examined predictors for repeated hyperkalemia among patients after first-time renin angiotensin system inhibitor (RASi) prescription, chronic kidney disease (CKD), or chronic heart failure (CHF); and we also examined potassium trajectories in these patients after their first hyperkalemia event. We used Danish population-based registries to identify all patients with first-time RASi prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
(25 reference statements)
1
31
1
4
Order By: Relevance
“…3,36 In patients with CKD and/or chronic HF receiving RAASi, risk factors for repeated hyperkalemia within 6 months of the first event include moderate to severe initial hyperkalemia (!5.6 mEq/L), low eGFR (<45 mL/min per 1.73 m 2 ), diabetes, and spironolactone use. 37 Hyperkalemia risk is slightly higher in men than in women after initiation of RAASi therapy 3 and differs among racial groups, in whom ethnicity, diet, and socioeconomic factors may contribute. 38 These factors currently do not impact hyperkalemia management; however, the potentially additive effects of these differences may increase hyperkalemia risk.…”
Section: Risk Factorsmentioning
confidence: 99%
“…3,36 In patients with CKD and/or chronic HF receiving RAASi, risk factors for repeated hyperkalemia within 6 months of the first event include moderate to severe initial hyperkalemia (!5.6 mEq/L), low eGFR (<45 mL/min per 1.73 m 2 ), diabetes, and spironolactone use. 37 Hyperkalemia risk is slightly higher in men than in women after initiation of RAASi therapy 3 and differs among racial groups, in whom ethnicity, diet, and socioeconomic factors may contribute. 38 These factors currently do not impact hyperkalemia management; however, the potentially additive effects of these differences may increase hyperkalemia risk.…”
Section: Risk Factorsmentioning
confidence: 99%
“…36 In previous literature, prior laboratory values for elevated serum potassium (K + ≥6 mmol/L) have also been shown to be a strong predictor of recurrent ED encounters for hyperkalemia. 27 Cumulative hours of dialysis in the prior 2 weeks and an average ultrafiltration rate ≥10 mL/kg/h were also significant predictors of ED encounters for hyperkalemia. Longer dialysis hours may be capturing an appropriate clinical response to treat patients with persistently elevated potassium, chronic volume overload, or uremic complications.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies have explored clinical and demographic factors associated with health care encounters for hyperkalemia, 27 - 29 while others have examined the health outcomes (particularly mortality) among hemodialysis patients with elevated serum potassium levels. 30 - 32 To our knowledge, this is the first multivariable prediction model that has been derived and internally validated to identify maintenance hemodialysis patients at increased risk for hyperkalemia-related ED encounters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large meta-analysis of real-world data conducted by Kovesdy et al,11 found that reduced eGFR and increased albumin-to-creatinine ratio, both indicative of kidney function impairment, were associated with the incidence of HK at both >5.0 and >5.5 mmol/l K + thresholds. Furthermore, low eGFR was also found to be a risk factor for recurrent HK (2nd or subsequent event defined as K + >5.0 mmol/L) in a population-based cohort study in Denmark 14. With regards to medication use, the use of ACEIs, ARBs, MRAs, and anti-hyperglycaemic agents was generally associated with increased risk of HK, while the use of diuretics (albeit not K + -sparing diuretics, which were considered separately and only retained in a single model) was generally protective against HK.…”
mentioning
confidence: 90%